Behaviour of reinforced concrete beams strengthened externally using pineapple leaf fibre (PALF) epoxy composite plate - Joyce, Ting Shu Qian (2016)
Reinforced concrete (RC) beams are often subjected to deterioration and degradation due to acid attack, overloading, poor construction condition and natural disasters. Repairing and retrofitting of RC beams are needed. The most traditional way to retrofit concrete element is externally bonding of steel plates to concrete. However it is more susceptible to corrosion and hard to install. The retrofitting technique commonly used to replace steel plates is synthetic fibre such as carbon, aramid and glass. Synthetic fibres are expensive and non-biodegradable. Hence, natural fibres are used to replace synthetic fibres towards environmental friendly and sustainable strengthening. The purpose of this research is to study the physical behaviour of pineapple leaf fibre (PALF) treated with different concentration (2%, 5% and 8%) of Sodium Hydroxide, to evaluate the flexural strength of PALF composite plate with epoxy of different volume ratio (0.1, 0.2, 0.3, 0.4) and the effectiveness of PALF-epoxy composite plate to RC beam. The experimental works carried out in the study were alkali (NaOH) treatment, Scanning Electron Microscope (SEM), single fibre test, flexural test of composite plates, and four-point loading test on beams. From the results, the tensile force for fibres treated with 2%, 5% and 8% NaOH decreased 40.8%, 56.3% and 68.2% as compared to untreated fibre. The increase in fibre content of composite samples from 20% to 40% increased the flexural strength by the range of 260% to 460% as compared to neat epoxy. The maximum flexural strength was obtained at fibre volume ratio of 40%. The research found that the beams with PALF-epoxy composite plate increased the flexural strength by 8% as compared to control beam when tested under four point loading system. The beam with PALF-epoxy composite plate has reduced its deflection by 74% at maximum load as compared to the control beam. In terms of crack pattern, PALF- epoxy composite plate has directed the crack to appear at the edge of the plate resulted in diagonal cracking. Hence, it is concluded that the PALF-epoxy composite plate is effective to be used as external strengthening material for retrofitting and rehabilitation of RC beams.